Impact of tolerance to fluconazole on treatment response in Candida albicans bloodstream infection. Issue 1 (15th October 2020) - Levinson, Tal; Dahan, Alon; Novikov, Anna; Paran, Yael; Berman, Judith; Ben‐Ami, Ronen
Abstract: Background: Treatment of Candida albicans bloodstream infection with fluconazole is associated with significant mortality despite in vitro susceptibility to the drug. Objectives: We sought to determine whether tolerance to fluconazole is predictive of treatment failure. Methods: We reviewed patients with monomicrobial C albicans bloodstream infection who received primary monotherapy with fluconazole. Tolerance to fluconazole, defined as the fraction of growth above the MIC, was quantified using the disc diffusion assay and digital image analyses. Survival analyses were performed with host and treatment factors as predictive variables. Results: Among 44 patients included in the study, all‐cause mortality was 29.5% at 30 days and 43.1% at 12 weeks. Forty‐one isolates (93%) were susceptible to fluconazole (MIC50, 0.5 mg/L). Fluconazole tolerance was strongly associated with death for patients treated with fluconazole within 24 h of candidemia onset (33.3% vs 0%; p = .007), but not among patients whose treatment was started later. MIC did not correlate with survival, regardless of treatment delay. A Cox regression model including time to treatment, tolerance to fluconazole, fluconazole exposure and Pitt bacteraemia score provided good prediction of treatment outcome (area under the receiver‐operator curve, 0.82). Conclusions: In patients with C albicans bloodstream infection, tolerance testing was predictive of fluconazole efficacy if the drug was started early. Further study is required to validate the utility of this metric to guide treatment choices.